NLRX1 Negatively Regulates Group A Streptococcus Invasion and Autophagy Induction by Interacting With the Beclin 1–UVRAG Complex - Aikawa, Chihiro; Nakajima, Shintaro; Karimine, Miho; Nozawa, Takashi; Minowa-Nozawa, Atsuko; Toh, Hirotaka; Yamada, Shunsuke; Nakagawa, Ichiro (Frontiers in Cellular and Infection Microbiology, 2018)
Group A Streptococcus (GAS) can invade epithelial cells; however, these bacteria are targeted and eventually destroyed by autophagy. Members of the Nod-like receptor (NLR) family are thought to be critical for the autophagic response to invasive bacteria. However, the intracellular sensors within host cells that are responsible for bacterial invasion and the induction of autophagy are largely unknown. Thus, our aim was to examine the role of one such NLR, namely NLRX1, in invasion and autophagy during GAS infection. We found that GAS invasion was markedly increased in NLRX1 knockout cells. This led to the potentiation of autophagic processes such as autophagosome and autolysosome formation. NLRX1 was found to interact with Beclin 1 and UVRAG, members of Beclin1 complex, and knockout of these proteins inhibited invasion and autophagy upon GAS infection. Especially, NLRX1 interacted with Beclin 1 via its NACHT domain and this interaction was responsible for the NLRX1-mediated inhibition of invasion and autophagic processes including autophagosome and autolysosome formation during GAS infection. These findings demonstrate that NLRX1 functions as a negative regulator to inactivate the Beclin 1–UVRAG complex, which regulates invasion and autophagy during GAS infection. Thus, our study expands our knowledge of the role of NLRX1 during bacterial invasion and autophagy and could lead to further investigations to understand pathogen–host cell interactions, facilitating novel targeted therapeutics.